Risk-sensitive Basel regulations and firms’ access to credit: Direct and indirect effects - Gopalakrishnan, Balagopal; Jacob, Joshy; Mohapatra, Sanket (Journal of Banking & Finance, 2021)
This paper examines the impact of risk-sensitive Basel regulations on debt financing of firms around the world. It investigates how firms cope with the impact through adjustments to their financing sources and capital investments. We find that the implementation of Basel II regulations is associated with reduced credit availability for lower-rated firms. Such firms mitigate the shortage in bank credit through increased reliance on accounts payable, lower payouts to shareholders, and reduced capital investments. The impact of the capital regulation is lower in countries that rely on the internal ratings-based approach. The key results are robust to controls for banking crises, bank-specific controls, and the inclusion of loan-level information. The findings of this paper substantially contribute to the understanding of the real effects of risk-sensitive bank capital regulations.